Consumption, consumption practices and consumerism: conceptualizations and the necessity of semantic delimitation - Lallas, Dimitris (The Greek Review of Social Research, 2019)
Given the various conceptualizations of the terms ‘consumption’ and ‘consumerism’, their confusion and, hence, the analytical distresses emerged in the study of consumer phenomenon this article aims to conceptualize ‘consumption’ in terms of social practice, and ‘consumerism’ as a dominant ethos and way of life in late-capitalist, consumerist societies. The proposed conceptualization of consumption practices aspires to avoid a priori negative/condemnatory or positive/celebratory semantic attributions and, moreover, to support locally sensible studies that give prominence to the special traits of those practices and the relations, constructed by means of consumption practices, with the world of objects, the self, the others, the natural and social world, and with social time and space